2009
DOI: 10.2310/7290.2009.00020
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Targeted Enhanced Ultrasound Imaging of Flk1 Reveals Diagnosis and Prognosis Potential in a Genetically Engineered Mouse Prostate Cancer Model

Abstract: Molecular imaging techniques used to detect the initiation of disease have the potential to provide the best opportunity for early treatment and cure. This report aimed at testing the possibility that Flk1+ (vascular endothelial growth factor receptor 2), a crucial angiogenesis factor of most tumor cells, could be a molecular targeted imaging marker for the diagnosis and prognosis of cancer. We performed Flk1-targeted microbubble-enhanced ultrasound (US) imaging of prostate cancer in a genetically engineered m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…In these studies, different tumors were used, such as human squamous cell carcinoma, 17 breast cancer, 16 human ovarian cancer, 19 orthotopic pancreatic tumor, 15 angiosarcoma, malignant glioma, 18 and prostate cancer. 46 The present study indicates that target-specific VEGFR2 binding microbubbles can be used for noninvasive in vivo visualization and detection of orthotopic prostate cancer in a rat tumor model. The results show that the specific contrast agent investigated could be of great interest for animal studies on new drugs directed against endothelial receptors.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In these studies, different tumors were used, such as human squamous cell carcinoma, 17 breast cancer, 16 human ovarian cancer, 19 orthotopic pancreatic tumor, 15 angiosarcoma, malignant glioma, 18 and prostate cancer. 46 The present study indicates that target-specific VEGFR2 binding microbubbles can be used for noninvasive in vivo visualization and detection of orthotopic prostate cancer in a rat tumor model. The results show that the specific contrast agent investigated could be of great interest for animal studies on new drugs directed against endothelial receptors.…”
Section: Discussionmentioning
confidence: 93%
“…In further studies, [15][16][17][18][19]46 it had been shown that molecular US using microbubbles binding to VEGFR2 allow visualization and quantification of angiogenesis and VEGFR2 expression in xenograft tumor models in mice. In these studies, different tumors were used, such as human squamous cell carcinoma, 17 breast cancer, 16 human ovarian cancer, 19 orthotopic pancreatic tumor, 15 angiosarcoma, malignant glioma, 18 and prostate cancer.…”
Section: Discussionmentioning
confidence: 98%
“…As a multiple biomarker associated with epithelium origin (very rarely arisen from mesenchymal tissue, see table 2) TRIM59 may be used as an EMT (epithelium–mesenchymal transition) specific cobiomarker. The TRIM59 antibody may also be used for molecular-targeted imaging as a new diagnostic marker, for example, in the context of targeted microbubble ultrasound destruction technology,23 before the protocol of a serum TRIM59 test can be established.
Strengths and limitations of this study

TRIM59 may be used a novel multiple tumor marker for immunohistochemical detecting early tumorigenesis and could direct a novel strategy for molecular-targeted diagnosis and therapy of cancer.

The work was mostly on human tumor samples by immunohistochemistry.

…”
Section: Discussionmentioning
confidence: 99%
“…22). In a transgenic mouse test of TRIM59 upregulation specifically in the prostate, TRIM59 demonstrated full oncogenic activity in directing tumorigenesis and progression to highest-grade CaP 17 23. The signal pathway of TRIM59 may be possibly linked with two large oncogene routes: the Ras/Raf/MEK/ERK/PI3K/AKT and the SV40 Tag/p53/pRB routes 17.…”
Section: Introductionmentioning
confidence: 99%
“…Microbubbles have been widely used as contrast agents to increase the blood backscatter in diagnostic ultrasound imaging [1]–[3]. More recently, it has been shown that microbubbles may also hold great potential for disease treatment, including oxygen delivery to hypoxic tissues [4], drug and gene delivery [5], [6], cavitation-assisted thrombolysis [7] as well as localized and transient opening of the blood–brain barrier (BBB) for targeted drug and gene delivery [8]–[10].…”
Section: Introductionmentioning
confidence: 99%